Analysis Influence of Religious Level on Islamic Business Behaviour of Food Micro Business Actors - Sucipto Febrianto; Ibnu Amin; Mursal Mursal; Nailur Rahmi; Anton Akbar (Journal of Islamic Economics and Finance Studies, 2025)
This study aims to test the three dimensions of religiosity, namely the dimensions of belief, worship and practice of Islamic business behaviour. The data used is primary data from questionnaires. Variable testing was carried out by classical assumption tests and statistical tests through the analysis of the spss 20 program. The partial test results in this study found that belief has a positive and significant effect on Islamic business behaviour with a t value of 2.288 greater than the t table of 1.66 and reinforced by a significance value of 0.003 <0.05. Worship has a positive and significant effect on Islamic business behaviour with a t value of 2.653 greater than the t table of 1.66 and reinforced by a significance value of 0.009 <0.05. Practicing has a positive and significant effect on Islamic business behaviour with a t value of 3.767 greater than the t table of 1.66 and strengthened by a significance value of 0.000 <0.05. Simultaneous test results in this study found that ideological variables, worship and practice variables simultaneously (simultaneously) affect the Islamic business behaviour variable. The test results obtained F count of 19.917 greater than the F table of 2.725 and reinforced by a significance value of 0.000 <0.05. From these results it is concluded that the aspect of belief as the first independent variable (X1), the aspect of worship as the second independent variable (X2) and the aspect of practice as the third independent variable (X3) simultaneously has a positive and significant effect on the dependent variable (Y), namely Islamic business behaviour. Together, religiosity has a significant influence on Islamic business behaviour. Religiosity arises from the recognition of truth by sincerity. Overall the traders have a different level of religiosity. This religious attitude fosters Islamic business behaviour in different ways. Although business behaviour is different, it does not violate the rules of Islamic business principles and ethics.